Inter-annual isotopic niche segregation of wild humboldt penguins through years of different El Niño intensities. (September 2019) - Chiu-Werner, Antje; Ceia, Filipe R.; Cárdenas-Alayza, Susana; Cardeña-Mormontoy, Marco; Adkesson, Michael; Xavier, José
Abstract: The Humboldt Current System presents high interannual variability, influenced by the El Niño Southern Oscillation (ENSO), whose implications in wildlife are not fully understood. We studied the isotopic niche of wild Humboldt penguins at Punta San Juan (Peru) during the pre-moult foraging trip in 4 consecutive years (2008–2011) under known oceanographic (ENSO) conditions. Our results show that there is a clear isotopic niche segregation (on both δ 13 C and δ 15 N values) of wild Humboldt penguins among all years. Besides isotopic niche segregation, niche width also varied significantly among years. The larger isotopic niche displayed in 2008 reflected the opportunistic feeding behaviour of Humboldt penguins when oceanographic conditions were unfavourable (i.e. El Niño of strong intensity). In contrast, and despite strong segregation, penguins displayed a more specialist behaviour in years of mild environmental conditions (i.e. 2009 "warm-weak", 2010 "neutral" and 2011 "warm-moderate"). No evidence of sexual segregation in wild Humboldt penguins during the pre-moulting foraging trip was found. This study highlights the coping mechanisms of an endangered species to changes in environmental conditions (i.e. overall, from strong to neutral El Niño events), which should have important ramifications in the management of the marine ecosystem in Peru, particularly the one related to the anchovy industry. Highlights: Strong inter-annual isotopic niche segregation in pre-moulting wild Humboldt Penguins. Significant variation in the isotopic niche width among years. No sexual segregation during the pre-moult foraging trip.